miR-6805-5p as a biomarker of cisplatin-induced nephrotoxicity in patients with head and neck cancer - Torso, Nadine De Godoy; Quintanilha, Julia Coelho França; Cursino, Maria Aparecida; Pincinato, Eder De Carvalho; Loren, Pía; Salazar, Luis A.; Lima, Carmen Silvia Passos; Moriel, Patricia (Frontiers in Pharmacology, 2023)
The standard treatment for head and neck squamous cell carcinoma (HNSCC) is cisplatinchemoradiotherapy. One of the main treatment adverse reactions is nephrotoxicity, for which there is currently no adequate specific and sensitive biomarker. Thus, this study aimed to evaluate the use of microRNAs (miRNAs) as renal biomarkers candidates. This was a retrospective cohort study. Nephrotoxicity was assessed through blood samples collected before and five days (D5) following chemotherapy. MiRNAs were extracted from urine samples collected at baseline and D5, and RNA sequencing identified miRNAs differentially expressed between participants with and without cisplatin-induced nephrotoxicity. 49 participants were included (n = 49). A significant difference was seen between the two groups for traditional renal markers (serum creatinine and creatinine clearance), and for the acute kidney injury (AKI) categories. Among the six miRNAs evaluated as biomarkers, four were upregulated (hsa-miR-6729-5p, hsa-miR-1238-5p, hsa-miR-4706, and hsa-miR-4322) and two were downregulated (hsa-miR-6805-5p and hsa-miR-21-5p), but only hsa-miR-6805-5p had a significant difference (p <0.0001). Its receiver operating characteristic curve revealed excellent specificity (0.920) for its expression fluctuation assessment, while its absolute expression in D5 showed greater sensitivity (0.792). So, the integrated use of these two parameters seems to be an interesting approach for AKI.